2019
DOI: 10.1186/s12906-019-2778-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral Guanxinshutong capsules in patients with stable angina pectoris in China: a prospective, multicenter, double-blind, placebo-controlled, randomized clinical trial

Abstract: BackgroundTo assess the efficacy and safety of oral Guanxinshutong (GXST) capsules in Chinese patients with stable angina pectoris (SAP) in a prospective, multicenter, double-Blind, placebo-controlled, randomized clinical trial (clinicaltrials.gov Identifier: NCT02280850).MethodsEligible patients were randomized 1:1 to the GXST or placebo group. Current standard antianginal treatment except for nitrate drugs was continued in both groups, who received an additional 4-week treatment of GXST capsule or placebo. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Rats were randomly divided into five groups ( n = 8 in each group): sham, middle cerebral artery occlusion, and MCAO + GXSTC pretreatment (0.5, 1.0, and 2.0 g/kg per day). These doses were chosen based on the dosage of GXSTC in clinical practice (0.3 g/capsule, 3 capsules once, 3 times a day) ( Li et al, 2019 ) and previous studies (0.5–2.0 g/kg in rats) ( Zhuo et al, 2012 ; Zhu et al, 2020 ). Rats in the sham and MCAO groups were pretreated with 0.9% saline solution, and rats in the GXSTC groups were pretreated with GXSTC (0.5, 1.0, and 2.0 g/kg per day, respectively) via intragastric administration for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were randomly divided into five groups ( n = 8 in each group): sham, middle cerebral artery occlusion, and MCAO + GXSTC pretreatment (0.5, 1.0, and 2.0 g/kg per day). These doses were chosen based on the dosage of GXSTC in clinical practice (0.3 g/capsule, 3 capsules once, 3 times a day) ( Li et al, 2019 ) and previous studies (0.5–2.0 g/kg in rats) ( Zhuo et al, 2012 ; Zhu et al, 2020 ). Rats in the sham and MCAO groups were pretreated with 0.9% saline solution, and rats in the GXSTC groups were pretreated with GXSTC (0.5, 1.0, and 2.0 g/kg per day, respectively) via intragastric administration for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has been used for thousands of years to prevent and treat CBVDs. Guanxin-Shutong capsule, a combination of Mongolian medicines and traditional herbs, has been commonly used to treat angina pectoris and coronary heart diseases in China (Li et al, 2019) (Rivera et al, 2014) at a weight ratio of 16:8:2:1:1 by weight. The major active components of GXSTC include phenolic acids, tanshinones, saponins, and others (Gao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the data showed that the safety of Shenzhu Guanxin Recipe was acceptable (22). A phase IV double-blind, randomized, and placebo-controlled study conducted at 12 centers in China indicated that after 4-week treatment with Guanxinshutong Capsule (冠 心 舒 通 胶 囊), the quality of life was substantially improved, and the number of angina attacks and the consumption of short-acting nitrates were significantly reduced (23). Both of these studies were based on the premise of standard western medication treatment with TCM, and there was no positive control group, so the study on Shengjie Tongyu Granule (升解通瘀颗粒) was born.…”
Section: Stable Anginamentioning
confidence: 99%
“…In an ischemia and reperfusion (MI/R) injury study, GXST significantly decreased levels of TNF- α , IL-1 β , and IL-6 and obviously inhibited NF- κ B activity in the MI/R model rat [ 14 ]. Furthermore, in a randomized clinical trial, GXST capsules are beneficial for the treatment of stable angina pectoris (SAP) patients [ 15 ]. It has also been shown that daily oral treatment of MI rats with GXST protects the heart against oxidative stress indicated by the increasing activities of total SOD, CATA, NOS and the levels of NO and GSH [ 16 ].…”
Section: Introductionmentioning
confidence: 99%